Black Phosphorus Nanosheets as a Neuroprotective Nanomedicine for Neurodegenerative Disorder Therapy. Issue 3 (30th November 2017) - Chen, Wansong; Ouyang, Jiang; Yi, Xinyao; Xu, Yan; Niu, Chengcheng; Zhang, Weiyu; Wang, Liqiang; Sheng, Jianping; Deng, Liu; Liu, You‐Nian; Guo, Shaojun
Abstract: Transition‐metal dyshomeostasis is recognized as a critical pathogenic factor at the onset and progression of neurodegenerative disorder (ND). Excess transition‐metal ions such as Cu 2+ can catalyze the generation of cytotoxic reactive oxygen species and thereafter induce neuronal cell apoptosis. Exploring new chelating agents, which are not only capable of capturing excess redox‐active metal, but can also cross the blood–brain barrier (BBB), are highly desired for ND therapy. Herein, it is demonstrated that 2D black phosphorus (BP) nanosheets can capture Cu 2+ efficiently and selectively to protect neuronal cells from Cu 2+ ‐induced neurotoxicity. Moreover, both in vitro and in vivo studies show that the BBB permeability of BP nanosheets is significantly improved under near‐infrared laser irradiation due to their strong photothermal effect, which overcomes the drawback of conventional chelating agents. Furthermore, the excellent biocompatibility and stability guarantee the biosafety of BP in future clinical applications. Therefore, these features make BP nanosheets have the great potential to work as an efficient neuroprotective nanodrug for ND therapy. Abstract : Black phosphorus (BP) nanosheets, having the capability of capturing Cu 2+ efficiently and selectively, can not only act as an antioxidant to extenuate cellular oxidative stress and inhibit cell apoptosis, but also improve the blood–brain barrier permeability under near‐infrared laser irradiation through the photothermal effect. These properties of BP nanosheets make them an efficient neuroprotective nanodrug for neurodegenerative disorder therapy.